Web-Based Online Queuing Information System at the Lendang Nangka Health Center - Muhammad Zamroni Uska; Yosi Nur Kholisho; Jamaludin; Rasyid Hardi Wirasasmita (Universitas Medan Area, 2023)
The online queuing system is a system that can make it easier for users through the administration process at the Lendang Nangka health center. However, the system implemented at the health center is still done manually, such as patients coming directly to the health center to register, and officers taking notes, and taking queues. So, this takes a long time and makes the dating patient feel bored and bored. The purpose of this study is to create a web-based online queuing system, system feasibility tester, user response and performance of this system. The model used for this study is ADDIE with five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques use questionnaires given to system experts and users. Meanwhile, the data analysis is used descriptively and uses the GT Metrix tool to see the efficiency of the system that has been created. Our findings are in the form of a web-based online queue information system that can facilitate the administrative process at this health center. In addition, this system is also categorized as very feasible and has a very high response. This system also includes grade A, where the performance result is 90%, and the structure are 90%. So that the system can help make it easier for patients, staff, and doctors in the administrative process at this health center.